Analisis Pengaruh Aliran Masuk Modal Asing Terhadap Pertumbuhan Ekonomi di Indonesia - Sari, Sekar; Satrianto, Alpon (Universitas Negeri Padang, 2024)
This study aims to analyze the effect of foreign capital inflows on economic growth in Indonesia. This study uses secondary data sourced from the World Bank and the Bank for International Settlements (BIS) from 1986-2021 using multiple linear regression analysis tools. The independent variables consist of foreign direct investment, foreign portofoio investment and foreign aid, with the control variables being inflation and interest rates and the dependent variable being economic growth. The results found that foreign direct investment has a positive and significant effect on economic growth. This shows that foreign capital inflows have an important role in encouraging economic growth. However, foreign portfolio investment has a negative effect on economic growth. Therefore, the monetary authority needs to implement a foreign capital inflow policy to maintain stability and encourage economic growth in Indonesia through foreign capital inflows. As well as implementing an effective and efficient governance system to reduce the misuse of foreign capital inflows so as to encourage economic growth.